A PARALLEL ASSESSMENT OF THE GROWTH PARAMETERS OF DIFFERENT LEGUMES GROWN IN CLODINAFOP STRESSED SOILS - Ahemad, Munees (Malaysian Journal of Science, 2012)
In modern agronomy, the indiscriminate and ill-advised application of herbicides leads to their accumulation in soils in substantial amounts and deteriorate the soil quality and fertility and in turn, the crop productivity. Earlier studies regarding the effect of herbicides were generally, restricted to a particular legume and studies about the concurrent impact of any specific herbicide on more than one legume are rare. This study was therefore, designed to evaluate the effect of the herbicide clodinafop simultaneously on four commonly grown food legumes (chickpea, pea, lentil and greengram). In this study, the growth of the selected legumes, in soils stressed with the recommended field application rate of clodinafop, decreased significantly. The root and shoot biomass, the symbiotic attributes (numbers, dry weight and leghaemoglobin content in nodules), nutrient-uptake (nitrogen and phosphorus), seed protein and yields of the tested legumes varied considerably in the presence of clodinafop. The toxic impact of clodinafop on nodule biomass, chlorophyll content, nutrient uptake and seed protein was marginal in all the tested legumes. In addition, clodinafop suppressed the root growth and seed yield in greengram, nodule numbers in pea and the shoot growth and leghaemoglobin content of nodules in chickpea. Overall, clodinafop showed the most adverse impact on the growth parameters of chickpea and greengram and the least on those of pea and lentil. (Keywords: herbicide, clodinafop, toxicity, legume, soil)